SISTEM INFORMASI AKUNTANSI BIAYA PRODUKSI PADA UD. KM ANUGRAH KENDAL - Sukemi Kamto Sudibyo; Sri Wahyuning; Evita Dwi Damayanti (CV. Denasya Smart Publisher, 2024)
KM Anugrah Kendal in handling production costs still uses manual estimates based on consideration of raw material notebooks and other costs with a calculator calculation tool which results in production cost information often being inaccurate so that the company has difficulty in determining the total costs that have been incurred. every time they do production and there is a delay in presentation. Up-to-date production cost reports make the process of controlling production costs difficult. UD. KM Anugrah Kendal must improve the existing production cost recording system, namely by implementing a new production cost accounting information system. A production cost accounting information system is the right choice to support the smooth implementation of the overall production cost handling system. By implementing a production cost accounting information system at UD. KM Anugrah Kendal has been able to determine the accuracy of production cost information so that it can handle production cost needs more precisely, quickly, accurately, effectively and efficiently to support UD's production process. KM Anugrah Kendal can be fulfilled so that the process of controlling production costs becomes easy.